Dental sleep-related conditions and the role of oral healthcare providers: A scoping review. (February 2023) - Huang, Zhengfei; Zhou, Ning; Lobbezoo, Frank; Almeida, Fernanda R.; Cistulli, Peter A.; Dieltjens, Marijke; Huynh, Nelly T.; Kato, Takafumi; Lavigne, Gilles J.; Masse, Jean-François; Pliska, Benjamin T.; van de Rijt, Liza; et al.
Abstract: Dental sleep medicine as a discipline was first described about a quarter of a century ago. Snoring, obstructive sleep apnea, sleep bruxism, xerostomia, hypersalivation, gastroesophageal reflux disease, and orofacial pain were identified as dental sleep-related conditions. This scoping review aimed to: i) identify previously unidentified dental sleep-related conditions; and ii) identify the role of oral healthcare providers in the prevention, assessment, and management of dental sleep-related conditions in adults. A systematic literature search was conducted in PubMed, Embase.com, Web of Science, and Cochrane. Studies that reported an actual or likely role of oral healthcare providers in the prevention, assessment, and/or management of sleep-related conditions were included. Of the 273 included studies, 260 were on previously listed dental sleep-related conditions; the other 13 were on burning mouth syndrome. Burning mouth syndrome was therefore added to the list of dental sleep-related conditions for the first aim and categorized into sleep-related orofacial pain. For the second aim, the role of oral healthcare providers was found to be significant in the prevention, assessment, and management of obstructive sleep apnea and sleep bruxism; in the assessment and management of snoring, sleep-related orofacial pain, and oral dryness; and in the assessment of sleep-related gastroesophageal reflux condition.